Hubungan Karakteristik Personal Pasien Dengan Lama Rawat Pasien Moderate Care Di Rumah Sakit Ortopedi Prof. Dr. R. Soeharso Surakarta - Dewi Sasmita, Elvira; , Arum Pratiwi, S.Kp, M.Kes (2017)
Lenght of stay is an indicator in the quality assessment of nursing service that reflects the delivery of nursing services has been optimal and in accordance with the needs of patients. Lenght of stay of patients in moderate care classification should be within 6-9 days, but there are different ranges in the Orthopedic Hospital Dr. R. Soeharso Surakarta in March 2017. The purpose of this research was to determine the relationship of personal characteristics of patients with long care patients in moderate care in the Orthopedic Hospital Dr. R. Soeharso Surakarta . The design of this research is descriptive correlative and approach method is cross section. With the sample used as many as 80 respondents with purposive sampling technique by determining the characteristics of the sample. Technique of data analysis used is somers'd correlation with result p value at factor under study <0,05 which can be concluded that there is correlation of personal characteristic of patient with long patient care of moderate care in Orthopedic Hospital Prof. Dr. Soeharso R. Surakarta